Analysis of Spectator Behavior in Matches on UFC YouTube Account - Abdallah, Mohammad Raja; Imawan, Khaerudin; Hermawan, Abdul Jalil; Ramadhan, Adam (ann4publisher@gmail.com, 2024)
This study examines audience behavior in Mixed Martial Arts (MMA) matches broadcast on the Ultimate Fighting Championship (UFC) YouTube channel. This theme was chosen because of the growing popularity of the UFC and YouTube's potential as a platform to reach a global audience. The study aims to identify the characteristics of viewers and content on UFC YouTube accounts, analyze audience interaction and engagement during broadcast MMA matches, and find out the motives or motivations of viewers in watching MMA matches on UFC YouTube. The research method used is qualitative, with a content analysis approach and observation of audience behavior in the YouTube comment column. The New Media Theory is a conceptual framework to understand this phenomenon. The results of the study show that UFC content on YouTube offers a variety of materials such as match highlights, full shows of the event, and exclusive content that appeals to global fans. Audience interaction in the comments section reflects intense engagement, including technical analysis of the match, emotional support for the fighter, and discussions between fans. The main motivations of spectators include interest in the sport itself, entertainment, inspiration, and support for favorite fighters. This research provides valuable insights into sports media consumption behavior in the digital era and the potential of online platforms in developing a sports fan base